2021
DOI: 10.1108/ajeb-03-2021-0033
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19, liquidity and financial health: empirical evidence from South Asian economy

Abstract: PurposeThe pandemic COVID-19 has affected every sector of an economy in every possible way. Banking sector of Bangladesh has been affected by it badly. The purpose of this paper is to find out the impact of COVID-19 on the liquidity and financial health of the listed banks in Bangladesh.Design/methodology/approachLiquidity ratios are calculated to measure the liquidity condition of the banks and revised Altman's Z-Score Model for non-manufacturing companies is used to measure the financial health. The ratios a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
2
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 17 publications
1
45
2
3
Order By: Relevance
“…This study found an effect of the current ratio on firm value in the pre-pandemic period, but did not find any effect during the pandemic period. Karim et al (2021) found that during the COVID-19 pandemic both conventional and Islamic banking experienced a decrease in the current ratio. Almost all banks in Bangladesh have a current ratio value of less than 1, which means that their financial condition is unfavorable.…”
Section: Ceccar Business Review Issn 2668-8921 • Issn-l 2668-8921mentioning
confidence: 99%
See 3 more Smart Citations
“…This study found an effect of the current ratio on firm value in the pre-pandemic period, but did not find any effect during the pandemic period. Karim et al (2021) found that during the COVID-19 pandemic both conventional and Islamic banking experienced a decrease in the current ratio. Almost all banks in Bangladesh have a current ratio value of less than 1, which means that their financial condition is unfavorable.…”
Section: Ceccar Business Review Issn 2668-8921 • Issn-l 2668-8921mentioning
confidence: 99%
“…At the same time, the speculative motive explains that the company's motivation to maintain liquidity is to gain profits on profitable investments in the future. Karim et al (2021) explained that during the pandemic there was a decline in the company's cash holdings that occurred due to the company's business disruption.…”
Section: Ceccar Business Review Issn 2668-8921 • Issn-l 2668-8921mentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, as part of the innovative strategies that SMEs are implementing, the home office is an action that is allowing adaptation to new ways of working. These activities and strategic actions are leading companies to improve their innovation management processes and above all to face current global challenges [138,139].…”
Section: Discussionmentioning
confidence: 99%